Drug‐induced liver injury at a tertiary care centre in Germany: Model for end‐stage liver disease is the best predictor of outcome. (8th July 2021) - Reike‐Kunze, Martin; Zenouzi, Roman; Hartel, Johannes; Krech, Till; Weidemann, Sören; Sterneck, Martina; Weiler‐Normann, Christina; Lohse, Ansgar W.; Schramm, Christoph; Sebode, Marcial
Abstract: Background & Aims: Agents most frequently inducing idiosyncratic drug‐induced liver injury (DILI) differ between countries worldwide. Besides, there is no consistent data on the best model predicting mortality or the need for liver transplantation in DILI. We here analysed the DILI cohort of our centre with regard to causative drugs and clinical outcome. Methods: A retrospective analysis of 157 consecutive severe DILI patients presenting to our tertiary care centre in Hamburg, Germany, from 2008 to 2018, was performed. Results: The most frequent putatively causative drugs were phenprocoumon (n = 21), metamizole (n = 17) and flupirtine (n = 6). The mean values of ALT, bilirubin and Model for End‐stage Liver Disease (MELD) score at the time of hospitalisation were 1201 U/L (SD: 1169 U/L), 6.8 mg/dL (SD: 7 mg/dL) and 17 (SD: 8). About 71% of all cases were treated with steroids or steroids combined with n ‐acetylcysteine. About 12.1% of all DILI cases had a poor outcome (liver transplantation and/or death). At the time of admission, MELD score performed better than Hy's law, the ratio (R) or the new ratio (nR) on their own or combined with bilirubin, regarding sensitivity or specificity for poor outcome. MELD score had a c‐statistic of 0.847 (95% CI: 0.731‐0.964). Furthermore, the cut‐off of 18 MELD points had a sensitivity of 88% and a specificity of 72% for poor outcome. Conclusion: Phenprocoumon and metamizole are frequent causative drugs for DILI in Germany. In comparison to other prognostic scores, MELD score ≥18 at the time of admission performed best in our cohort for the prediction of poor outcome in DILI.